The Effect of Ambassador's Brand, and Brand Image on Purchase Decision Process in E-Commerce Tokopedia - Annisa Sulihandini; Eka Askafi; Sumarji (Global Writing Academica Researching & Publishing, 2022)
The purpose of this study is to discover and explain the effects of Brand Ambassador and Brand Image on the Purchase Decision Process, as well as to discover and explain that the Brand Ambassador variable has a partial effect on the Purchase Decision Process. An explanatory research type and a quantitative approach are used in this study. A total of three variables were examined in this research: Brand Ambassadors (X1), Brand Image (X2), and the Purchase Decision Process (PDP) (Y). Tokopedia customers were asked to fill out an online survey as a means of obtaining data. The sample used in this study amounted to 116 respondents with the respondent's criteria, namely respondents knew E-Commerce Tokopedia and had shopped online through E-Commerce Tokopedia. Descriptive and multiple linear regression analysis are utilized as sampling methods. The results demonstrated that the purchase decision process (Y) was highly influenced by both the Brand Ambassador (X1) and Brand Image (X2) variables at the same time. Then, the influence of Brand Ambassador (X1) and Brand Image (X2) variables on the Purchase Decision Process is partial and significant (Y).